MRI for the detection of small malignant renal masses: a systematic review and meta-analysis - Shang, Wenwen; Hong, Guohui; Li, Wei (Frontiers in Oncology, 2023)
Objective: We aimed to assess available evidence on the diagnostic performance of magnetic resonance imaging for differentiating malignant small renal masses from benign. Methods: An electronic literature search of Web of Science, MEDLINE (Ovid and PubMed), Cochrane Library, EMBASE, and Google Scholar was performed to identify relevant articles up to January 31, 2023. We included studies reporting the diagnostic accuracy of using magnetic resonance imaging for differentiating small (≤4 cm) malignant renal masses from benign. The pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio were calculated using the bivariate model and the hierarchical summary receiver operating characteristic model. The study quality evaluation was performed with the Quality Assessment of Diagnostic Accuracy Studies-2 tool. Results: A total of 10 studies with 860 small renal masses (815 patients) were included in the current meta-analysis. The pooled sensitivity and specificity for studies detection of malignant masses were 0.85 (95% CI 0.79-0.90) and 0.83 (95% CI 0.67-0.92), respectively. Conclusions: MRI had moderate diagnostic performance for detecting malignant small renal masses from those of benign. Substantial heterogeneity was observed between studies for both sensitivity and specificity.